The effect of sex on multiple sclerosis risk and disease progression. (April 2020) - Voskuhl, Rhonda R
Sex differences in the incidence or severity of disease characterize many autoimmune and neurodegenerative diseases. Multiple sclerosis is a complex disease with both autoimmune and neurodegenerative aspects and is characterized by sex differences in susceptibility and progression. Research in the study sex differences is a way to capitalize on a known clinical observation, mechanistically disentangle it at the laboratory bench, then translate basic research findings back to the clinic as a novel treatment trial tailored to optimally benefit each sex. This "Bedside to Bench to Bedside" approach based on sex differences in MS will be reviewed here, first for disease susceptibility then for disability progression.